Żaden cud nie jest mniejszy ...”. Sakralizacje w poezji Ireny Dowgielewicz - Krysińska, Katarzyna (In Gremium. Studies in History, Culture and Politics, 2015)
„No miracle is smaller ...”. Sacralizati on mainstream in the literary of Irena Dowgielewicz The topic of this article is the sacred of Irena Dowgielewicz’s writings. It is visible especially in the poems from volumes Sowing parsley (1963) and Stadium for ladybird (1970). Religiosity of these texts can be seen in various aspects. The author refers to the particular conception of God and heaven, to the relationship between man and Creator, but also to the primary sacrum. Among the elements and features of religious mainstream in Dowgielewicz’ poetry, a few intertwining ones can be distinguished: perception of world’s transcendent dimension and God’s presence; items elevation; sacralization of everyday life and everyday activities; God’s creatures participation in the act of creating reality; sanctification of rich and full of contrasts nature; canonization of memory of the past; elevation of homeland and of the earth-mother; transmission of pain; relatives’ sacralization; sanctification of motherhood and marriage; interpenetration of God’s creatures and works; consideration of life in the categories of the gift and the miracle; humble looking at the world, sensitivity, simplicity of expression and personal relationship with God. The poems of Irena Dowgielewicz sanctify almost every component of the reality created by God. Such sacralization mainstream builds a space of harmony and sense.